Stock Market Performance during Covid-19 Lockdown : A Descriptive Analysis of Nepal Stock Exchange - Pokhrel, Sagar (Adhyayan Journal, 2023)
This article aims to investigate how the Nepalese stock market behaved during the government-imposed closure to combat COVID 19. In order to analyze the secondary data from March 2020 to September 2021, the time period was divided into three parts: first part is the first lockdown period, second part is the time following the first lockdown and the time before the second lockdown, and the third part is the second lockdown period. The Nepse Index was used as the dependent variable in an OLS regression, while the sub-indices were used as the independent variables. To reduce the issue of heteroscedasticity, all the study variables were transformed into their natural logarithmic forms. Since the study’s variables were time series data, the stationarity test was also carried out to produce reliable OLS regression findings. The findings show that the lockdown imposed by the government owing to COVID 19 caused a sharp decline in the share price of all indices on the Nepalese stock market. However, as soon as the lockdown was released, the market began to recover, and the share values began to rise significantly. The findings show that banking and non-life insurance have a significant positive impact on Nepse performance over all three periods, even if the impact of finance was never felt during the study period. Using the study’s informative data, investors can manage their share portfolio in unexpected and bad circumstances.